Education in the age of artificial intelligence: How will technology shape learning? - SIAU, Keng (Institutional Knowledge at Singapore Management University, 2018)
The age of Artificial Intelligence (AI) is here! Higher education needs to prepare students for a world in which AI plays an increasingly dominant role. What are the jobs that can be replaced easily? How would higher education be affected in the age of AI, robotics, machine learning, and automation? How can higher education excel and flourish in the age of AI?